2002
DOI: 10.1016/s0893-133x(01)00405-5
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Lysergic Acid Diethylamide Influences Gene Expression Patterns within the Mammalian Brain

Abstract: Hallucinogenic drugs such as lysergic acid diethylamide (LSD) have profound effects on humans including INTRODUCTIONLysergic acid diethylamide (LSD) is an hallucinogenic drug that transiently but powerfully alters human perception, behavior, and mood at extremely low doses. Certain aspects of the behavior elicited by acute doses of LSD closely resemble symptoms of mental disorders such as schizophrenia (Breier 1995). Despite extensive research over the past four decades, the mechanism of action of hallucinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 39 publications
3
104
0
2
Order By: Relevance
“…145,146]. Homer1a or Ania-3 mRNA expression is increased within PFC and/or NAC upon acute injection of psychomotor stimulants [102,[159][160], the hallucinogen LSD [161,162], nicotine [163], and the dissociative anesthetic phencyclidine [164]. While the repeated administration of cocaine or nicotine induces a tolerance in the capacity of the drug to elevate NAC Homer1a levels [160,163], the capacity of methamphetamine to elevate mRNA levels persists within PFC with repeated drug treatment [159].…”
Section: Homers Are Regulated Within Addiction-related Neural Circuitmentioning
confidence: 99%
“…145,146]. Homer1a or Ania-3 mRNA expression is increased within PFC and/or NAC upon acute injection of psychomotor stimulants [102,[159][160], the hallucinogen LSD [161,162], nicotine [163], and the dissociative anesthetic phencyclidine [164]. While the repeated administration of cocaine or nicotine induces a tolerance in the capacity of the drug to elevate NAC Homer1a levels [160,163], the capacity of methamphetamine to elevate mRNA levels persists within PFC with repeated drug treatment [159].…”
Section: Homers Are Regulated Within Addiction-related Neural Circuitmentioning
confidence: 99%
“…First described for acute cocaine (Brakeman et al, 1997), a growing number of studies demonstrate an enhancement within corticolimbic structures in the expression of mRNA encoding short Homer isoforms by acute exposure to psychoactive drugs Cochran et al, 2002;Fujiyama et al, 2003;Nichols et al, 2003;Nichols and Sanders-Bush, 2002;Polese et al, 2002). Although there is some evidence that the capacity of drugs of abuse to increase short Homer isoform expression is enduring (Ammon et al, 2003;Cochran et al, 2002) or persists throughout repeated drug administration (Ammon et al, 2003;Fujiyama et al, 2003), behavioral sensitization to methamphetamine is not coincident with an altered capacity of this drug to elevate the expression of short Homer isoforms (Fujiyama et al, 2003).…”
Section: Homer Proteins and Behavioral Sensitivity To Drugsmentioning
confidence: 99%
“…Interestingly, the specific 5HT 2A receptor activation caused by hallucinogens seems to be of key importance in producing neuroplasticity. Hallucinogens Drug-Induced Neuroplasticity such as LSD induce brain-region dependent mRNA expression of various immediate early genes, such as c-Fos, arc, and homer1a splice isoform ania3 (Nichols and Sanders-Bush, 2002), that influence regulation of gene expression and synaptic responses, whereas DOI has been shown to produce changes in dendritic spine morphology on cortical neurons . Chronic LSD administration to rats causes a persistent increase in synthesis and turnover of 5-HT as well as downregulation of cortical 5HT 2A receptors (Diaz and Huttunen, 1971;Lee and Geyer, 1980;Gresch et al, 2005), and a 2-week LSD treatment followed by 14 days of abstinence still showed an augmented 5-HT level in the midbrain and cerebral cortex (Peters and Tang, 1977).…”
Section: Behavioral Effects and Addiction Potentialmentioning
confidence: 99%